Добровольці на обороні Маріуполя: бойові дії в секторі «М» у вересні 2014 року і участь в них українських добровольчих формувань (Серія: Історія. Політологія, 2021)
У статті з’ясовується роль українських добровольчих формувань в бойових діях в секторі «М» у вересні 2014 року. Основу джерельної бази дослідження складають аналітичні матеріали Генерального Штабу Збройних Сил України, видання, упорядковані за сприяння Департаменту комунікацій Міністерства внутрішніх справ України, спогади учасників подій та внутрішня документація добровольчих батальйонів. The article examines the course of hostilities in Sector "M" in September 2014, as well as the participation of Ukrainian volunteer formations in them. The source base of the study is based on analytical materials of the General Staff of the Armed Forces of Ukraine, publications organized with the assistance of the Communications Department of the Ministry of Internal Affairs of Ukraine, memoirs of participants and unregulated documentation of volunteer battalions. The aim of the publication is to to find out the role of Ukrainian volunteer formations in hostilities in Sector M in early September 2014. To achieve this goal, the article examines the sources that cover this topic, identifies the list of Ukrainian volunteer formations stationed at the time in Sector "M", and the nature of their participation in military operations. The research methodology involves the application of the principles of historicism, the usage of studying whole historical sources and being objective. Descriptive method, methods of classification and systematization as well as methods of analysis and synthesis have been used. The scientific novelty is caused by unexplored topics within academic science. It’s the first scientific review of hostilities on the Azov coast in the first days of autumn 2014. The prospects of further research is that by studying the course of hostilities in this strategically important section of the front, it is possible to analyze in more detail the military-political events of the period under study as a whole. The conclusions of the study are to determine the key role of Ukrainian volunteer formations (primarily the Azov Battalion and the Cossack unit in the border detachment (Т.Shevchenko’s Kyiv cossack regiment), as well as volunteer battalions "Shakhtarsk" and "Slobozhanshchina" and some crews of the Dnipro-1 battalion) in the defense of Mariupol on September 4-5, 2014. Given the strategic importance of the Azov section of the front, it is possible to state the significant contribution of volunteer formations to the military-political events of autumn 2014 in general.